DEVELOPMENT AND VALIDATION FOR NEW ANALYTICAL METHOD OF DAPAGLIFLOZIN BY RP-HPLC - Anjali Chaudhary, Dr. Rita Saini, Dr. Shivanand Patil (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
An innovative approach has been developed and validated for HPLC analysis of Dapagliflozin. This method was verified based on ICH guidelines, encompassing accuracy, linearity, precision, and robustness. The UV spectra of the standard solution were analyzed across the wavelength range of 200 nm to 400 nm, revealing the isobestic point at 205 nm. The Dapagliflozin peak was successfully separated using a mobile phase comprising 65:35 v/v of buffer and acetonitrile, with the buffer pH set to 3.8 using either orthophosphoric acid or sodium hydroxide, achieving optimal retention time, peak area, and symmetry. All analytical parameters were appraised using a Shimadzu C18 column (15 cm × 4.6 mm internal diameter, 5 µm particle size), ensuring the Dapagliflozin peak was distinctly resolved at a wavelength of 205 nm. Dapagliflozin exhibited a retention time of 6.986 minutes, with a flow rate of 0.8 ml/minute and a sample volume of 10µl. The regression coefficients (r2) were found to be 0.99985 for the standard solution and 0.99947 for the test solution, both meeting the acceptable criteria. The assay recovered rate assorted between 99.10% and 101.71%.